Traumatic Globe Subluxation Accompanied by Traumatic Optic Neuropathy. Issue 7 (October 2020) - Kim, Woojin; Yang, Sungwon; Park, Jinhwan; Lee, Hwa; Baek, Sehyun
Abstract : Abstract: A 52-year-old, alcohol-intoxicated woman suffered periorbital trauma to the left eye and presented to the emergency department with proptosis and complaints of decreased vision in the left eye. Physical examination revealed loss of light perception (LP), relative afferent pupillary defect (RAPD), pupil dilatation, and corneal epithelial defect of the left eye. In addition, the fundus of the left eye was not easily visible due to severe corneal abrasion and edema, but there was no retinal detachment or vitreous hemorrhage on B-scan ultrasonography. Hertel exophthalmometric values differed by 7 mm between the eyes and measured 13 mm in the right eye and 20 mm in the left eye. In addition, she had severely limited left eye movement in all directions. Computerized tomography (CT) imaging of the orbit showed that the left optic nerve extended 15 mm further than the optic nerve of the right eye and retrobulbar hemorrhage of the left eye. The patient underwent emergency lateral canthotomy, cantholysis, and conjunctival incision to release the optic nerve extension and reduce the eyeball subluxation of the left eye. An intraoperative examination demonstrated that all extraocular muscles of the left eye were intact. The left eyeball returned to its normal position after surgery. Two days after surgery, proptosis of the left eye improved significantly, and there was no difference in Hertel exophthalmometric values between the eyes, both eyes measured 13 mm. However, the patient continued to suffer LP, RAPD, and pupil dilatation of the left eye.